FOOD COMPOSITION AND NICHE CHARACTERISTIC OF GIANT FEATHERBACK (Chitala lopis, Bleeker 1851) IN KAMPAR RIVER, INDONESIA - Arif Wibowo; Ridwan Affandi; Dwi Atminarso (Indonesian Fisheries Research Journal, 2014)
This paper provides information on the diets of Chitala lopis in Kampar River, Riau Province based on study conducted from Mei 2009 to November 2010. Fish species were obtained from fishers using modified nets, traps, hooks and lines. Specimens were cold with cool box at the point of collection and transported to the laboratory. A total of 176 fish specimens were inspected and their stomach contents were examined. The month-wise collection and experiments were made to exhibit the seasonal variation in food preferences, and feeding habit of the fish. Frequency of occasion and numerical methods were used in this study. Results of denote that C. lopis fed on juvenile fish, shrimp, plant material, insects, worms, benthos, gravel and unidentified organism. The consumption of shrimp tends to increase due to giant featherback’s size, which relates to wider mouth, energy, location (water depth) and gonad development, also there is an increase of shrimp consumption during dry season. In giant featherback, the percentage of consumed shrimps is associated with sex and season, meanwhile the consumption of small fish and plant material is related to fish’s size, sampling station and maturity index. Giant featherback tends to be more selective consuming certain food’s group while growing.